Human Platelet Lysate Acts Synergistically With Laminin to Improve the Neurotrophic Effect of Human Adipose-Derived Stem Cells on Primary Neurons in vitro - Guiotto, Martino; Raffoul, Wassim; Hart, Andrew M.; Riehle, Mathis O.; di Summa, Pietro G. (Frontiers in Bioengineering and Biotechnology, 2021)
Background Despite the advancements in microsurgical techniques and noteworthy research in the last decade, peripheral nerve lesions have still weak functional outcomes in current clinical practice. However, cell transplantation of human adipose-derived stem cells (hADSC) in a bioengineered conduit has shown promising results in animal studies. Human platelet lysate (hPL) has been adopted to avoid fetal bovine serum (FBS) in consideration of the biosafety concerns inherent with the use of animal-derived products in tissue processing and cell culture steps for translational purposes. In this work, we investigate how the interplay between hPL-expanded hADSC (hADSChPL) and extracellular matrix (ECM) proteins influences key elements of nerve regeneration. Methods hADSC were seeded on different ECM coatings (laminin, LN; fibronectin, FN) in hPL (or FBS)-supplemented medium and co-cultured with primary dorsal root ganglion (DRG) to establish the intrinsic effects of cell–ECM contact on neural outgrowth. Co-cultures were performed “direct,” where neural cells were seeded in contact with hADSC expanded on ECM-coated substrates (contact effect), or “indirect,” where DRG was treated with their conditioned medium (secretome effect). Brain-derived nerve factor (BDNF) levels were quantified. Tissue culture plastic (TCPS) was used as the control substrate in all the experiments. Results hPL as supplement alone did not promote higher neurite elongation than FBS when combined with DRG on ECM substrates. However, in the presence of hADSC, hPL could dramatically enhance the stem cell effect with increased DRG neurite outgrowth when compared with FBS conditions, regardless of the ECM coating (in both indirect and direct co-cultures). The role of ECM substrates in influencing neurite outgrowth was less evident in the FBS conditions, while it was significantly amplified in the presence of hPL, showing better neural elongation in LN conditions when compared with FN and TCPS. Concerning hADSC growth factor secretion, ELISA showed significantly higher concentrations of BDNF when cells were expanded in hPL compared with FBS-added medium, without significant differences between cells cultured on the different ECM substrates. Conclusion The data suggest how hADSC grown on LN and supplemented with hPL could be active and prone to support neuron–matrix interactions. hPL enhanced hADSC effects by increasing both proliferation and neurotrophic properties, including BDNF release.